The Role of Teachers in Increasing Reading Interest of Primary Schools Through Literation in The Pandemic Time Covid-19 - Fauziah, Fitriana Bunga; Suhandi, Andi (International Conference on Elementary Education, 2021)
The implementation of education in Indonesia during the COVID-19 pandemic has experienced several visible changes. The health crisis caused by the COVID-19 outbreak has spearheaded online learning concurrently. In this case, the role of the teacher is to guide and to help students in solving the problems which they face regarding their knowledge. Reading is a language skill that is very important in our life. Reading has an important role in giving birth to an intelligent, creative, and critical next generations. By reading, someone can get knowledge and information from all over the world. Reading is a must for individuals who instill themselves as an intellectual. The purpose of this study is to determine the role of teachers in creating literacy in Indonesian subjects. This study uses interview techniques and based on the results of the research that has been done, an effort to build reading literacy for children is through the role of the teacher. The role of the teacher to improve reading literacy is by giving rules, giving orders, giving rewards, facilitating, modeling, guiding, motivating, giving affection, and let the students free to choose their reading sources and materials.